An epidemiological study of injury among urban population - Ghimire, A; Nagesh, S; Jha, N; Niraula, SR; Devkota, S (Kathmandu University Medical Journal, 2010)
Background: Injuries are a focus of public health practice because they pose a serious health threat, occur frequently and are preventable. Injuries affect people of all ages and range from minor cuts and bruises to major catastrophes that take thousands of lives. Objectives: This paper aims to find out the prevalence of injuries and to study the various epidemiological factors related to the injuries in Dharan. Materials and methods: A sample of 1398 households was taken as study sample. A systematic random sampling technique was used to select the 10% households from each 19 wards. A pre-tested questionnaire was used to collect demographic information and information related to injuries to the persons suffered from injuries. Result: The prevalence of minor injury in Dharan was 3.5% per month. The injury was common in the age group, 40-49 years (4.6%) and majority of injured persons were farmers (6.9%). Home was the common place (55.6%) for the minor injury. Cut/stab (32.8%) was the most common types of minor injury. The prevalence of major injury was 0.7% per year and occurred more among 50-59 years age group (1.7%). The commonest place for major injury was at road (53.1%) and service holders were at more risk (1.4%). Falls from the height (46.9%) were the most common types of major injury. Conclusion: The injuries related to lifestyle profession and road traffic accidents (RTA) is the commonest burden revealed in the study sample. Promotion of safety and education for protection at work and safe driving can prevent the major socio-economic loss to the family and community at large. Key words: Minor injury; Major injury; RTA; Epidemiological factors. DOI: 10.3126/kumj.v7i4.2762 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 402-407